Penguatan Karakter Siswa melalui Kurikulum Berbasis Cinta: Studi Kasus di Pondok Pesantren - Buya Riadi; Yuniar Yuniar; Firmansyah Firmansyah; Mardiah Astuti (Al-Munawwarah : Jurnal Pendidikan Islam, 2026)
This study aims to analyze the implementation of the Compassion-Based Curriculum in strengthening students’ character in an Islamic boarding school setting and to identify the supporting and inhibiting factors influencing its implementation. The study employed a qualitative descriptive method by collecting data through observation, interviews, and documentation involving school leaders, teachers, students, dormitory supervisors, and parents. The findings indicate that compassion values were integrated into classroom learning, religious habituation, pesantren culture, and students’ daily interactions. The principal and teachers played an active role in fostering empathy, discipline, responsibility, and mutual respect through both instructional activities and school culture. The implementation process was supported by a strong collective commitment among school members, a conducive boarding school environment, and parental involvement. Nevertheless, differences in students’ backgrounds and external social influences remained challenges in maintaining sustainable character development. This study demonstrates that the Compassion-Based Curriculum provides a meaningful approach to integrating emotional, spiritual, and social values within Islamic boarding school education.